Determinants of maternal knowledge on developmental milestones of children attending immunization clinics in the district of Colombo, Sri Lanka - Fazla Fayaz; Sampatha Goonawardane (Journal of the College of Community Physicians, 2017)
Background: It is accepted that a good start at the beginning of life makes a child to be an efficient person of the society, hence the first five years is a crucial period of child’s growth and development. Therefore, the mother should have adequate knowledge about child’s development.   Objective: To assess the knowledge on developmental milestones and its determinants among mothers of eighteen-month old children in Kolonnawa and Dehiwala Medical Officer of Health (MOH) areas in the district of Colombo.   Methods: A descriptive cross-sectional study was conducted among 421 mother-child pairs of 18-months attending government immunization clinics. All study participants who are eligible were taken into the study. An interviewer-administered-questionnaire was used to assess knowledge on the assessment of developmental milestones on a pre-determined scoring system and its potential determinants. Univariate and multivariate analyses were performed.   Results: Knowledge on the assessment of developmental milestones was ‘good’ among 74% of mothers. Unmarried, divorced and separated mothers were 10 times more at risk for poor knowledge compared to married women (OR=10.3; 95% CI=1.9, 55.4). Mothers living in nuclear families were 2.5 times more likely to be less knowledgeable than the others (OR=2.5; 95% CI=1.4, 3.3). Higher-educational-level of mothers showed a significant protective effect (OR=0.6; 95% CI=0.3, 0.9). A higher proportion of mothers who had no access to formal health information had poor knowledge on developmental milestones, showing a 2.5 fold risk than mothers who gained formal health information (OR=2.5; 95% CI=1.1, 6.0). However, only 2.7% utilized the child health development record (CHDR) for getting information on child’s development.   Conclusions: A majority of mothers had good knowledge on the assessment of developmental milestones. Mothers should be encouraged to utilize the CHDR and should emphasis the importance of recording milestones. Vulnerable population such as unmarried, divorced/separated mothers and mothers living without family support need targeted education.